Association Between Paternal Alcohol Consumption Before Conception and Anogenital Distance of Offspring. (14th February 2018) - Xia, Ruilan; Jin, Longmei; Li, Dekun; Liang, Hong; Yang, Fen; Chen, Jianping; Yuan, Wei; Miao, Maohua
Abstract : Background: There are limited studies on the effects of paternal alcohol consumption, before conception, on the reproductive development of offspring. Anogenital distance (AGD), the distance from the center of the anus to the genitals, is a sensitive biomarker of reproductive hormone abnormalities during the critical developmental window. The relationship between paternal alcohol consumption and AGD of human offspring has not been studied yet. Methods: This cohort study included 1, 292 pregnant women recruited in Shanghai. An in‐person interview was conducted to collect information on demographic characteristics of couples, and husbands' lifestyles, including drinking habits. AGD (boys, AGD‐AP [anus‐penis], AGD‐AS [anus‐scrotum]; girls, AGD‐AC [anus‐clitoris], AGD‐AF [anus‐fourchette]) measurements were performed at birth, and at 6 and 12 months of age. Multiple linear regression analysis was conducted to determine the association between paternal alcohol consumption before conception, and the AGDs of offspring. Results: Data included AGD measurements of infants at birth ( N  = 980), at 6 months ( N  = 592, 60.4%), and at 12 months ( N  = 543, 55.4%). Boys in the paternal alcohol‐exposed group had shorter AGDs, irrespective of the areas measured (AGD‐AP and AGD‐AS) and time of measurements, than those in the unexposed group. However, only the differences in AGD‐AP at birth and AGD‐AS at 6 months were statistically significant. For girls, the associations were similar at birth; however, the AGD‐AC and AGD‐AF were longer in the paternal alcohol‐exposed group than the unexposed group at 12 months. Conclusions: Our findings provide first, but preliminary evidence, that paternal alcohol consumption within 3 months before conception may be associated with shorter AGD in the offspring, especially in boys, which indicates that paternal alcohol drinking may have an adverse effect on their reproductive development. Further studies should be conducted to validate these results. Abstract : Paternal alcohol consumption before conception has been shown to have adverse health effects on offspring, but the effects on human reproductive development remain unknown. This population‐based cohort study showed that paternal alcohol consumption before conception may be associated with shorter Anogenital Distance(AGD) –a sensitive biomarker of reproductive development abnormalities–in the offspring, especially in boys. The study provides first epidemiological evidence that paternal alcohol drinking may have an adverse effect on the reproductive development of offspring.